2005
DOI: 10.1093/aob/mci062
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and Intra-specific Variation among Five Erythroxylum Taxa Assessed by AFLP

Abstract: There is a heterogeneous genetic structure among the cultivated Erythroxylum taxa where E. coca and E. novogranatense are two independent species. Erythroxylum coca var. coca is most likely the ancestral taxon of E. c. var. ipadu and a founder effect may have occurred as E. c. var. ipadu moved from the eastern Andes in Peru and Bolivia into the lowland Amazonian basin. There is an indication of artificial hybridization in coca grown in Colombia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 16 publications
(59 reference statements)
6
16
0
Order By: Relevance
“…The cultivated species form a unique clade with no exceptions. This point has been echoed in previous published phylogenic work with cultivated Erythroxylum species totaling over 150 unique accessions (Johnson et al 2003b(Johnson et al , 2005. However, our analysis does reveal a sister clade of four non-cultivated species as the most closely related to the cultivated species.…”
Section: Relationships Among Cultivated Erythroxylum Taxasupporting
confidence: 76%
See 3 more Smart Citations
“…The cultivated species form a unique clade with no exceptions. This point has been echoed in previous published phylogenic work with cultivated Erythroxylum species totaling over 150 unique accessions (Johnson et al 2003b(Johnson et al , 2005. However, our analysis does reveal a sister clade of four non-cultivated species as the most closely related to the cultivated species.…”
Section: Relationships Among Cultivated Erythroxylum Taxasupporting
confidence: 76%
“…If En is derived from Ec, one would expect a lower level of genetic diversity in the derived species compared to what is usually found in putative progenitor-derivative species pairs (e.g., Ranker and Schnabel 1986). However, Johnson et al (2005) found equally high levels of genetic diversity in Ec and En, thus challenging Plowman's (1979b) hypothesis. In light of the high levels of genetic diversity and the long period of cultivation for both species (Plowman 1984), the morphological similarity between them may be attributed to artificial selection rather than shared ancestry and may thus indicate two separate domestication events.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Cocaine is extracted from four different cultivated Erythroxylum taxa (E. coca variety coca, E. novogranatense variety novogranatense, E. coca variety ipadu and E. novogranatense variety truxillense [1]). Several recipes enabling the extraction of cocaine from the coca leaf exist, with particular names, such as the ''ollado'' method, the ''Chimore 2005'' or the ''Colombia 2000'' one, etc.…”
Section: Introductionmentioning
confidence: 99%